Selection of phage-displayed human antibody fragments specific for CD1b presenting the Mycobacterium tuberculosis glycolipid Ac2SGL. Issue 2 (June 2016) - Camacho, Frank; Sarmiento, María E.; Reyes, Fatima; Kim, Louise; Huggett, Jim; Lepore, Marco; Otero, Oscar; Gilleron, Martine; Puzo, Germain; Norazmi, Mohd Nor; Rook, Graham; Mori, Lucia; et al.
Abstract: Objective/background: The development of new tools capable of targeting Mycobacterium tuberculosis (Mtb)-infected cells have potential applications in diagnosis, treatment, and prevention of tuberculosis. In Mtb-infected cells, CD1b molecules present Mtb lipids to the immune system (Mtb lipid–CD1b complexes). Because of the lack of CD1b polymorphism, specific Mtb lipid–CD1b complexes could be considered as universal Mtb infection markers. 2-Stearoyl-3-hydroxyphthioceranoyl-2′-sulfate-α-α′-d -trehalose (Ac2 SGL) is specific for Mtb, and is not present in other mycobacterial species. The CD1b–Ac2 SGL complexes are expressed on the surface of human cells infected with Mtb. The aim of this study was to generate ligands capable of binding these CD1b–Ac2 SGL complexes. Methods: A synthetic human scFv phage antibody library was used to select phage-displayed antibody fragments that recognized CD1b–Ac2 SGL using CD1b-transfected THP-1 cells loaded with Ac2 SGL. Results: One clone, D11—a single, light-variable domain (kappa) antibody (dAbκ11)—showed high relative binding to the Ac2 SGL–CD1b complex. Conclusion: A ligand recognizing the Ac2 SGL–CD1b complex was obtained, which is a potential candidate to be further tested for diagnostic and therapeutic applications.